The Influence of Leadership and Work Environment on Job Satisfaction and Its Impact on Employee Performance - Assiddiki, Abdel Hakim (International Journal of Business, Management and Economics, 2023)
This study aims to find out and analyze the Influence of Leadership and Work Environment on Job Satisfaction and Its Impact on Employee Performance of PT. Sri Aneka Karyatama Palembang. The object of this study is all employees at PT. Sri Aneka Karyatama Palembang. The research method used in this study is associative by using primary data as the main data and secondary data as supporting data. The population in this study is employees of each division in PT. Sri Aneka Karyatama Palembang has as many as 417 people. The sample obtained through the Slovin formula is 205 employees with sampling techniques using proportionate simple random sampling. The data analysis technique used in this study is path analysis with direct effect and indirect effect testing. The results showed that leadership has a positive and significant effect on job satisfaction, the Work environment has a positive and significant effect on job satisfaction, has a positive and significant effect on employee performance, the work environment has a positive and significant effect on employee performance, leadership job satisfaction has a negative and insignificant effect on employee performance, leadership through job satisfaction has a positive and significant effect on employee performance, work environment through job satisfaction has a negative and insignificant effect on employee performance.